Validation of OraQuick HCV Rapid Antibody Test in Postmortem Specimens. Issue 2 (June 2020) - Rose, Claire E.; Duncan, Lisa; Hawes, Amy M.
INTRODUCTION: The objective of this study is to evaluate the performance of OraQuick HCV Rapid Antibody Test against a "gold-standard", FDA-approved, laboratory-based serum immunoassay (SI) in postmortem blood. To date, OraQuick HCV Rapid Antibody Test has not been evaluated for use in postmortem testing. This OraQuick test is a manually performed, visually interpreted, single use immunoassay for the qualitative detection of antibodies to the hepatitis C virus (HCV). METHODS: Blood was collected from 51 decedents whose deaths were investigated in the jurisdiction of the Knox and Anderson County Medical Examiner's Office (MEO) January 2017 through April 2017. For each consented case, blood was tested using both the OraQuick HCV Rapid Antibody Test and a laboratory-based hepatitis C serum immunoassay ("gold standard" reference assay). Results from the OraQuick HCV Rapid Antibody Test were compared against a laboratory-based hepatitis C serum immunoassay. RESULTS: Using the laboratory-based serum immunoassay (SI) as the "gold standard" for assessing true HCV antibody positivity, and comparing SI against OraQuick rapid test, sensitivity for the OraQuick rapid test was 95.65% and specificity was 96.15% in postmortem blood. DISCUSSION: Our results demonstrate that OraQuick HCV rapid antibody test is reliable for diagnosis of hepatitis C infection in postmortem blood with a relatively short (less than approximately 21.5 hours) postmortem sample acquisition time. The OraQuick in some cases may be superior to traditional, laboratory-based HCV SI due to potential increased viscosity of postmortem blood.